Evaluation of food function in children microcephaly by Zika Virus: two-year follow-up (Research, Society and Development, 2021)
The sequelae of microcephaly vary according to the severity of the lesion, however, there are few reports of food function in children with microcephaly caused by Zika virus. Objective: to evaluate the food function in children with Zika virus microcephaly. Forty-three children diagnosed with SCZ microcephaly were evaluated, divided into three groups, according to the age range of the children, understood as follows: Age Range 1 (FE1) aged between 0 and 6 months; Age group 2(FE2) aged between 6 months and 1 day to 36 months; Age group 3(FE3) aged between 36 months and 1 day to 48 months. Specific aspects of the child's feeding and eating behavior were analyzed, as well as speech therapy assessment. The evaluations were defined by the protocol created by the clinical service, given the absence of validated protocols for the studied sample. For the analysis, the results were presented in simple and absolute percentage distribution. Signs suggestive of aspiration were more frequent in FE2, while in FE1 and 3 there was a lower incidence of children with this sign of impairment in swallowing. In the evaluation of swallowing with pasty food was observed during food uptake, altered lip occlusion in FE2 and 3. in 45.5% of children in age group 2 and 45.8% in age group 3. Presence of extraoral escape, time of oral transit, coughing, post-swallowing residues, laryngeal elevation and, with a lower incidence, the suggestive signs of aspiration in FE2 and 3. It was possible to conclude that there were important alterations in the functions of sucking and swallowing. These findings indicate that this population should be kept under multidisciplinary follow-up.